Global Current Practices of Ventilatory Support Management in COVID-19 Patients: An International Survey - Alqahtani JS; Mendes RG; Aldhahir A; Rowley D; AlAhmari MD; Ntoumenopoulos G; Alghamdi SM; Sreedharan JK; Aldabayan YS; Oyelade T; Alrajeh A; Olivieri C; et al. (Journal of Multidisciplinary Healthcare, 2020)
Jaber S Alqahtani,1,2 Renata G Mendes,3 Abdulelah Aldhahir,1,4 Daniel Rowley,5 Mohammed D AlAhmari,2,6 George Ntoumenopoulos,7 Saeed M Alghamdi,8,9 Jithin K Sreedharan,2 Yousef S Aldabayan,10 Tope Oyelade,11 Ahmed Alrajeh,10 Carlo Olivieri,12 Maher AlQuaimi,13 Jerome Sullivan,14 Mohammed A Almeshari,15 Antonio Esquinas16 1UCL Respiratory, University College London, London, UK; 2Department of Respiratory Care, Prince Sultan Military College of Health Sciences, Dammam, Saudi Arabia; 3Department of Physical Therapy, Cardiopulmonary Physiotherapy Laboratory, Federal University of São Carlos, São Paulo, Brazil; 4Respiratory Care Department, Faculty of Applied Medical Sciences, Jazan University, Jazan, Saudi Arabia; 5Pulmonary Diagnostics & Respiratory Therapy Services, University of Virginia Medical Center, Charlottesville, VA, USA; 6Dammam Health Network, Dammam, Saudi Arabia; 7Consultant Physiotherapist, Physiotherapy Department St Vincent’s Hospital Sydney, Sydney, NSW, Australia; 8National Heart and Lung Institute, Imperial College London, London, UK; 9Faculty of Applied Medical Sciences, Umm Al-Qura University, Makkah, Saudi Arabia; 10Respiratory Care, King Faisal University, Al-Ahsa, Saudi Arabia; 11UCL Institute for Liver and Digestive Health, London, UK; 12Emergency Department, Ospedale Sant’Andrea, Vercelli 13100, Italy; 13Imam Abdulrahman Bin Faisal University, Dammam, Saudi Arabia; 14President, International Council for Respiratory Care, Professor Emeritus & Respiratory Care Program Director, The University of Toledo, Toledo, OH, USA; 15Rehabilitation Health Sciences Department, College of Applied Medical Sciences, King Saud University, Riyadh, Saudi Arabia; 16Director International NIV School, Intensive Care Unit, Hospital Morales Meseguer, Murcia, SpainCorrespondence: Jaber S AlqahtaniUCL Respiratory, University College London, Rowland Hill Street, London NW3 2PF, UKEmail Alqahtani-Jaber@hotmail.comBackground: As the global outbreak of COVID-19 continues to ravage the world, it is important to understand how frontline clinicians manage ventilatory support and the various limiting factors.Methods: An online survey composed of 32 questions was developed and validated by an international expert panel.Results: Overall, 502 respondents from 40 countries across six continents completed the survey. The mean number (±SD) of ICU beds was 64 ± 84. The most popular initial diagnostic tools used for treatment initiation were arterial blood gas (48%) and clinical presentation (37.5%), while the national COVID-19 guidelines were the most used (61.2%). High flow nasal cannula (HFNC) (53.8%), non-invasive ventilation (NIV) (47%), and invasive mechanical ventilation (IMV) (92%) were mostly used for mild, moderate, and severe COVID-19 cases, respectively. However, only 38.8%, 56.6% and 82.9% of the respondents had standard protocols for HFNC, NIV, and IMV, respectively. The most frequently used modes of IMV and NIV were volume control (VC) (36.1%) and continuous positive airway pressure/pressure support (CPAP/PS) (40.6%). About 54% of the respondents did not adhere to the recommended, regular ventilator check interval. The majority of the respondents (85.7%) used proning with IMV, with 48.4% using it for 12– 16 hours, and 46.2% had tried awake proning in combination with HFNC or NIV. Increased staff workload (45.02%), lack of trained staff (44.22%) and shortage of personal protective equipment (PPE) (42.63%) were the main barriers to COVID-19 management.Conclusion: Our results show that general clinical practices involving ventilatory support were highly heterogeneous, with limited use of standard protocols and most frontline clinicians depending on isolated and varied management guidelines. We found increased staff workload, lack of trained staff and shortage of PPE to be the main limiting factors affecting global COVID-19 ventilatory support management.Keywords: COVID-19, ventilation, respiratory, clinical management, proning, mechanical ventilation, NIV, HFNC